Dipyrone in association with atropine inhibits the effect on gastric emptying induced by hypoglycemia in rats - Collares,E.F. (2017)
Atropine (AT) and dipyrone (Dp) induce a delay of gastric emptying (GE) of liquids in rats by inhibiting muscarinic receptors and activating β2-adrenergic receptors, respectively. The objective of the present study was to determine the effects of pretreatment with AT and Dp, given alone or in combination, on the effect of hypoglycemia in the liquid GE in rats. Male Wistar adult rats (280-310 g) were pretreated intravenously with AT, Dp, AT plus Dp or their vehicle and then treated 30 min later with iv insulin or its vehicle (n=8-10 animals/group). Thirty min after treatment, GE was evaluated by determining, in awake rats, the percent gastric retention (%GR) of a saline meal labeled with phenol red administered by gavage. The results indicated that insulin induced hypoglycemia in a dose-dependent manner resulting in a significant reduction in %GR of liquid only at the highest dose tested (1 U/kg). Pretreatment with AT significantly increased %GR in the rats treated with 1 U/kg insulin. Surprisingly, after pretreatment with AT, the group treated with the lowest dose of insulin (0.25 U/kg) displayed significantly lower %GR compared to its control (vehicle-treated group), which was not seen in the non-pretreated animals. Pretreatment with Dp alone at the dose of 40 mg/kg induced an increase in %GR in both vehicle and 0.25 U/kg-treated rats. A higher dose of Dp alone (80 mg/kg) significantly reduced the effect of a marked hypoglycemia induced by 1 U/kg of insulin on GE while in combination with AT the effect was completely abolished. The results with AT suggest that moderate hypoglycemia may render the inhibitory mechanisms of GE ineffective while Dp alone and in combination with AT significantly overcame the effect of hypoglycemia on GE.